Can Chinese herbal medicine offer feasible solutions for newly diagnosed esophageal cancer patients with malnutrition? a multi-institutional real-world study - Lu, Yi-Chin; Tseng, Liang-Wei; Wu, Chiao-En; Yang, Ching-Wei; Yang, Tsung-Hsien; Chen, Hsing-Yu (Frontiers in Pharmacology, 2024)
Background: Esophageal cancer (EC) is a major cause of cancer-related mortality in Taiwan and globally. Patients with EC are highly prone to malnutrition, which adversely affects their prognosis. While Chinese herbal medicine (CHM) is commonly used alongside conventional anti-cancer treatments, its long-term impact on EC patients with malnutrition remains unclear.Methods: This study utilized a multi-center cohort from the Chang Gung Research Database, focusing on the long-term outcomes of CHM in EC patients with malnutrition between January 1, 2001, and December 31, 2018. Patients were monitored for up to 5 years or until death. Overall survival (OS) rates were calculated using the Kaplan-Meier method. Overlap weighting and landmark analysis were employed to address confounding and immortal time biases. Additionally, the study analyzed prescription data using a CHM network to identify key CHMs for EC with malnutrition, and potential molecular pathways were investigated using the Reactome database.Results: EC patients with malnutrition who used CHM had a higher 5-year OS compared with nonusers (22.5% vs. 9% without overlap weighting; 24.3% vs. 13.3% with overlap weighting; log-rank test: P=0.006 and 0.016, respectively). The median OS of CHM users was significantly longer than that of nonusers (19.8 vs. 12.9 months, respectively). Hazard ratio (HR) analysis showed a 31% reduction in all-cause mortality risk for CHM users compared with nonusers (HR: 0.69, 95% confidence interval: 0.50-0.94, P=0.019). We also examined 665 prescriptions involving 306 CHM, with Hedyotis diffusa Willd. exhibiting the highest frequency of use. A CHM network was created to determine the primary CHMs and their combinations. The identified CHMs were associated with the regulation of immune and metabolic pathways, particularly in areas related to immune modulation, anti-cancer cachexia, promotion of digestion, and anti-tumor activity.The results of this study suggest a correlation between CHM use and improved clinical outcomes in EC patients with malnutrition. The analysis identified core CHMs and combinations of formulations that play a crucial role in immunomodulation and metabolic regulation. These findings lay the groundwork for more extensive research on the use of CHM for the management of malnutrition in patients with EC.